2021
DOI: 10.1097/cnj.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Health First Aid for Self-Care

Abstract: : Nurses who provided care to patients with coronavirus (COVID-19) and supported patients in their transition from life to death in the absence of patients' families have been especially needful of spiritual self-care. A spiritual first aid kit can help nurses cope with these difficult times. Spiritual self-care is vital for all nurses to renew and preserve the psychological, spiritual, and physical self.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…There was no differentiation between the in-person and virtual R&R making it difficult to explain how barriers were determined by each participant. Of note, other studies of self-care and professional self-care report “time” as a barrier, with a connection to “leadership support” (Green, 2021; Lier et al, 2019; Ross, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There was no differentiation between the in-person and virtual R&R making it difficult to explain how barriers were determined by each participant. Of note, other studies of self-care and professional self-care report “time” as a barrier, with a connection to “leadership support” (Green, 2021; Lier et al, 2019; Ross, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that one source of nurses' strength is God or their faith in God during difficulties. Similarly, Green (2021) revealed that powerlessness should not be viewed as a weakness but as an avenue to ask for God's support.…”
Section: Discussionmentioning
confidence: 99%
“…As nurses deal with their patient's pain and suffering, it also affects their physical, emotional, and spiritual well-being (Groves & Klauser, 2009). Resultantly, nurses often neglect their physical, emotional, and spiritual well-being (Green, 2021). Due to these challenges and issues nurses confront during this pandemic, nurses may find themselves losing control over their working environment, which could affect how they behave, think, and feel about the present and future situations at work.…”
Section: Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Spirituality can encompass values, beliefs, and religions, in addition to providing meaning to life, connection with others, and life purpose, being a transcendental or metaphysical phenomenon that correlates with the purpose and meaning of life (29). In nursing care, the dimension of spiritual health and self-care is supported by studies that emphasize the importance of the therapeutic dimensions of spirituality (30).…”
Section: Discussionmentioning
confidence: 99%